Juno's first glimpse of Jupiter's complexity. Issue 15 (10th August 2017) - Bolton, Scott; Levin, Steven; Bagenal, Fran
Abstract: Preliminary results from NASA's Juno mission are presented in this special issue of Geophysical Research Letters. The data were gathered by nine scientific instruments as the Juno spacecraft approached Jupiter on the dawn flank, was inserted into Jupiter orbit on 4 July 2016, and made the first polar passes close to the planet. The first results hint that Jupiter may not have a distinct core, indicate puzzling deep atmospheric convection, and reveal complex small‐scale structure in the magnetic field and auroral processes that are distinctly different from those at Earth. Key Points: Juno's polar, eccentric orbit provides a unique close‐up view of Jupiter Juno's science payload addresses key issues of the magnetosphere, atmosphere, and deep interior of Jupiter The first passes are revealing unexpected atmospheric structure and auroral processes